MR Spectroscopy Detects Lipid Peaks in Cerebrotendinous Xanthomatosis - Embiruçu, E.K.; Otaduy, M.C.G.; Taneja, A.K.; Leite, C.C.; Kok, F.; Lucato, L.T. (American Journal of Neuroradiology, 2010)
SUMMARY: CTX is a rare lipid-storage disease. Novel MRS findings from 3 patients, using a short TE, were the presence of lipid peaks at 0.9 and 1.3 ppm in the depth of the cerebellar hemisphere; this might represent an additional marker of disease that is CNS-specific and noninvasive. A decrease in NAA concentration was also detected and attributed to neuroaxonal damage. One patient presented an increase in mIns concentration, pointing to gliosis and astrocytic proliferation. a.u.arbitrary unitChocholine-containing compoundsCNScentral nervous systemCrcreatine/phosphocreatineCTXcerebrotendinous xanthomatosisLiplipidLip09lipid signals at 0.9 ppmLip13lipid signals at 1.3 ppmmInsmyo-inositolMRSMR spectroscopyNAAN-acetylaspartatePRESSpoint-resolved spectroscopy sequenceSTEAMshort echo time stimulated echo acquisition modeVOIvolume of interest